Cybersafety in education for the 21st century: A comparative study of Malaysia and Thailand - Soon , Seng Thah; Kaur, Kuldip; Ling, Philip (2019)
Education for the 21st Century must recognise cybersafety issues faced by students in schools. Cybersecurity threats are everywhere and students must be able to cope with an environment where cyber threats and risks persist. What are these threats and risks and how do students in Malaysia and Thailand handle them? This paper attempts to compare and contrast cybersafety issues among school students in Malaysia and Thailand. The sample for this survey comprised 1,896 students from Malaysia and 1,336 students from Thailand. The quantitative research approach was used to explore and confirm relationship among variables. Four important factors influencing cybersafety among students in Malaysia comprise i. availability of help through significant others, parents and teachers (including counsellors), ii. accessing negative sites, iii. tendency to hide things from parents, and iv. feeling of discomfort when surfing negative sites. On the other hand, factors in Thailand include: i. ready availability of help if bullied or proper avenues are available, ii. victim of cyberbullying, iii. experiences of cyberbullying, and iv. experiences with accessing negative websites. The findings showed high construct reliability and high construct validity which was confirmed through Structural Equation Modeling. The study showed that Malaysia and Thailand’s cybersafety issues differed significantly (p < .05) in 6 constructs, i.e. i. existence of problematic situations or negative experiences, ii. peer pressure, iii. parent-children gap, iv. sexting, v. cyber-bullying, and vi. dealing with negative experience or mediation strategies. The study recommended the following: i. parents in both Malaysia and Thailand should play a pivotal role in their children’s well-being in cybersafety issues, ii. Malaysia and Thailand should develop local-based strategies to suit local contexts in cybersafety issues, and iii. overcoming new cyber risks in Malaysia and Thailand should follow best practices in other countries which have successfully overcome them. (Abstract by authors)